Contribution of molecular diagnosis to the management of cutaneous leishmaniasis in travellers. (8th January 2014) - Lavergne, R. A.; Iriart, X.; Martin‐Blondel, G.; Chauvin, P.; Menard, S.; Fillaux, J.; Cassaing, S.; Roques‐Malecaze, C.; Arnaud, S.; Valentin, A.; Magnaval, J. F.; Marchou, B.; et al.
Abstract Cutaneous leishmaniasis is one of the most frequent skin diseases occurring after travelling in endemic areas. Optimal management requires identification of the species of Leishmania involved. In this study we aimed to evaluate the use of molecular diagnosis as routine, in comparison with direct examination and culture. Thirty positive diagnoses were carried out between 2007 and 2013. Classical PCR enabled 11 positive cases to be identified that were found to be negative by conventional methods. Sequencing led to the identification of eight different species. Routine use of PCR and sequencing appears very efficient in the management of cutaneous leishmaniasis.